Morphological Variability in White and Black-White Clams From Amal Beach, Tarakan: A Comparative Analysis - Sumarlin, Sumarlin; Gaffar, Syamsidar (Jurnal Harpodon Borneo, 2021)
Morphological characteristics are crucial for understanding the biology and ecology of marine species like clams. In this study, we aimed to investigate and compare the morphological differences between white and black-white clams using various morphometric measurements. To ensure accurate and reliable data, we examined 13 morphological traits, including shell length (SL), shell height (SH), shell width (SW), umbo length (UL), ligament length (LL), anterior length (AL), posterior length (PL), length of cardinal tooth (LCT), length of posterior adductor scar to anterior adductor scar (LPAS), pallial line scar to ventral margin anterior (PVM), adductor scar width scar (AW), posterior adductor scar width scar (PW), and an additional character of pallial sinus open scar (PS) shape for their normality and homogeneity. Our findings showed that most of the data followed a normal distribution according to the Shapiro-Wilk test, but there were some exceptions. Shell Width (SW), Length of Cardinal Tooth (LCT), Length of Posterior Adductor Scar to Anterior Adductor Scar (LPAS), Posterior Adductor Scar Width (PW), and Pallial Sinus Open Scar (PS) did not follow a normal distribution. This might be due to factors like different sample sizes, outliers, or a limited number of samples. Also, variables like Posterior Length (PL), Anterior Length (AL), Adductor Scar Width (AW), and Pallial Line Scar to Ventral Margin Anterior (PVM) were non-homogeneous. We found that white clams had moderate morphological variability with values below 30%, while black-white clams showed inconsistent variability, with some values above 30%. An independent sample t-test was performed on four variables: SL (Shell Length), SH (Shell Height), LL (Ligament Length), and UL (Umbo Length). The results indicated no significant morphological differences between white and black-white clams for these measured traits. This finding suggests that the morphological characteristics examined in this study are not influenced by the shell color differences between the two clam groups. For future studies, we suggest increasing sample sizes, using alternative testing methods more tolerant to data non-normality, and addressing factors causing data heterogeneity.